The Relationship of Mother's Attitude and Husband's Support with the Selection of a Delivery Place in Mulyorejo Village, Silo District, Jember Regency - Ika Nurdiana; Yuniasih Purwaningrum; Syaiful Bachri (D'Nursing and Health Journal (DNHJ), 2023)
Introduction: In 2021, at Mulyorejo there are 16.05% of mothers who are not using medical facilities. A mother died after giving birth at home. This study aims to study the relationship of mother's attitude and husband's support with the selection of a place of birth for mother-in-law at Mulyorejo district Silo district Jember. Method: This research uses survey research design with cross-sectional design, its sampling technique is simple random Sampling. The sample consisted of 64 respondents. The study was conducted in March 2022 at Mulyorejo. Data analysis with Chi-Square. Result: 1) The majority of mothers were positive (56.25%). The majority of the support of the husband is good support (84.37%). The majority of births are in health facilities (76.6%). 4) There is a relationship between the attitude of the mother and the choice of the place of birth for the mother in the village of Mulyorejo district of Jember with p-value = 0,000, coefficient of contingency = 0,479. 5) There is a relationship between the support of the husband and the selection of the place of birth of the mother in the village of Mulyorejo district of Jember with p-value = 0,001, coefficient contingent = 0.388. Coclusion: The more positive the mother's attitude and the better the support of the spouse will make the mother more likely to choose to give birth in a health facility.